2022
DOI: 10.1371/journal.pone.0272618
|View full text |Cite
|
Sign up to set email alerts
|

Dietary practices and nutritional status of young children in the former ensete monoculture dominated Sidama region, southern Ethiopia: A community based cross-sectional study

Abstract: Background Child undernutrition is a challenge in Ethiopia, where morbidity and mortality among children are attributed to it. This study aimed to describe the dietary practices, household food insecurity, and nutritional status of young children in Dale district, Sidama region, southern Ethiopia. We discuss our findings in light of research from the same area 3 to 5 decades ago, and we analyze factors associated with linear growth of young children. Method A community-based cross-sectional study design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Although no food taboos were reported in this study, other studies in Ethiopia reported social norms and beliefs as common barriers to ASF consumption among young children and mothers ( Haileselassie et al, 2020 ). Even though the majority of the households keep hens, the prevalence of childhood stunting was high (39.5%) in our recent publication about the nutritional status of the children in the area ( Behailu et al, 2022 ). This finding may suggest that households mainly keep hens for the production of eggs for sale, rather than egg consumption at household level ( Daba et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although no food taboos were reported in this study, other studies in Ethiopia reported social norms and beliefs as common barriers to ASF consumption among young children and mothers ( Haileselassie et al, 2020 ). Even though the majority of the households keep hens, the prevalence of childhood stunting was high (39.5%) in our recent publication about the nutritional status of the children in the area ( Behailu et al, 2022 ). This finding may suggest that households mainly keep hens for the production of eggs for sale, rather than egg consumption at household level ( Daba et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…This study included a sample of 851 children aged 6–24 months and caregivers (primarily the mother) out of 971 children aged 0–24 months and caregivers enrolled in a larger study (Household food security and dietary practices in the rural Dale district, southern Ethiopia). Study procedures, including the original sample size estimation, sampling procedures and recruitment are described in a previous article ( Behailu et al, 2022 ). A census, household listing, proportionality according to kebele size, and simple random sampling were performed.…”
Section: Methodsmentioning
confidence: 99%